EMPOWERMENT OF HOUSEHOLD MOTHERS IN MAJAPAHIT VILLAGE THROUGH CREATIVITY IMPROVEMENT FOR INCREASING INCOME FOR FAMILY - Nining Asniar Ridzal; Waode Adriani Hasan; Waode Erna; Anita Anita; Siti Rahayu (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Dalam kehidupan nyata perempuan seringkali kurang mampu berperan aktif dalam perekonomian keluarga, akibatnya perempuan hanya bekerja sebagai ibu rumah tangga dan bergantung pada penghasilan suami. Kaum perempuan yang memiliki kemampuan mandiri di bidang ekonomi adalah salah satu indikator meningkatnya kesejahteraan. Ketika perempuan mengenyam pendidikan, memiliki hak milik, dan kebebasan untuk bekerja baik diluar maupun di dalam rumah serta mandiri. Tujuan pengabdian masyarakat mengajak para ibu rumah tangga yang memiliki banyak waktu tidak produktif di Kelurahan Majapahit untuk berkreasi guna menciptakan produk yang bernilai ekonomis. Sehingga diharapkan suatu saat nanti masyarakat bisa menjadi pengusaha sukses. Metode Pelaksanaan dengan memberikan pengetahuan dan materi. Hasil dari Pengabdian ini adalah kegiatan ini dapat memberikan tambahan pengetahuan dan wawasan tentang peluang usaha bagi ibu-ibu rumah tangga, dengan modal kecil dan menggunakan peralatan yang sudah ada, sehingga dapat menambah pendapatan keluarga. Selain itu, ibu-ibu rumah tangga sudah memiliki keinginan untuk berwirausaha.Abstract: In real life women are often less able to play an active role in the family economy, as a result women only work as housewives and depend on their husbands' income. Women who have the ability to be independent in the economic field is one indicator of increasing welfare. When women receive education, have property rights, and the freedom to work both outside and inside the home and be independent. The purpose of community service is to invite housewives who have a lot of unproductive time in Majapahit Village to be creative in order to create products that have economic value. So hopefully one day people can become successful entrepreneurs. Implementation method by providing knowledge and materials. The result of this service is that this activity can provide additional knowledge and insight about business opportunities for housewives, with small capital and using existing equipment, so that they can increase family income. In addition, housewives already have the desire to become entrepreneurs.